A Case of Intrathoracic Gastric Duplication Cyst Detected on Prenatal Ultrasound Examination - Hisako Yagi; Yoshino Kinjyo; Yukiko Chinen; Hayase Nitta; Tadatsugu Kinjo; Keiko Mekaru; Hitoshi Masamoto; Hideki Goya; Tomohide Yoshida; Naoya Sanabe; Yoichi Aoki (Case Reports in Obstetrics and Gynecology)
A 37-year-old (G4P3) woman was referred to our hospital at 32 weeks of gestation for the evaluation of a fetus with an intrathoracic cystic lesion. Ultrasonography and magnetic resonance imaging revealed that a fetal cystic lesion without a mucosal layer was located in the posterior mediastinum. These findings were consistent with a bronchogenic cyst. At 38 3/7 weeks of gestation, an elective cesarean section was performed because of her previous cesarean section. A female neonate without any external anomalies, weighing 2,442 g, with Apgar scores of 8 and 9, and requiring no resuscitation was born. Four weeks after delivery, the neonate was admitted because of respiratory distress due to mass effect. At right lateral thoracotomy, a 105 × 65 mm of solitary smooth-walled cyst containing serosanguineous fluid was found in the posterior mediastinum, which was excised completely. Histologic examination revealed the diagnosis of the mediastinal gastric duplication cyst. The neonate made an uneventful recovery. Accurate diagnosis is not necessary, but detection and continuous observation are logical. Although gastric duplication, particularly intrathoracic, is a rare pathology, it should be considered in the differential diagnosis of any intrathoracic cyst.